A regulamentação do enfoque comercial no setor educacional via OMC/GATS - Ângela C. de Siqueira (Revista Brasileira de Educação, 2004)
groups growing interest in the educational field given the large amount of resources involved, presenting the perspective of including education, as a service, on the agenda of the General Agreement on Trade in Services, as a World Trade Organisation directive. To this end, it analyses WTO and GATS documents, as well as proposals presented by some countries, demonstrating their interests in eliminating barriers to free trade in education. The text points out that the existence of national regulations and even the offer of public education can be challenged as practices which are harmful to the free offer of educational services and subject to WTO sanctions allowing business groups to demand public resources and other benefits. Should GATS succeed, it runs the risk of converting education from a subjective public right into a process of simple commercialisation of educational packages (e.g. courses, systems of evaluation and certification, textbooks, uniforms, maps etc.). It concludes by indicating that such a perspective clearly endangers national sovereignty and autonomy, leading potentially to the loss of cultural diversity and local values, to the benefit of a process of cultural homogeneity. Notwithstanding, it also highlights the emergence of movements opposing this tendency.